Team Effectiveness in Community-Based Teams: Gotong Royong as Cultural Social Capital and Teamwork as a Mediating Process - Suroso; Citra Savitri; Rengga Madya Pranata; Enjang Suherman; Ade Mubarok (Global Research Collaboration, 2026)
This research investigates how gotong royong culture contributes to team effectiveness by examining teamwork as a mediating process in community-based student teams. The study is framed by Social Capital Theory and uses a quantitative explanatory survey involving 91 KKN teams in the Purwasukasi area of Indonesia. The data were processed with Partial Least Squares Structural Equation Modeling (PLS-SEM), including mediation analysis. The results show that gotong royong culture significantly improves teamwork (β = 0.52, p < 0.001) and has a smaller but significant direct effect on team effectiveness (β = 0.21, p < 0.05). Teamwork is the strongest predictor of team effectiveness (β = 0.62, p < 0.001). The model accounts for 26.5% of teamwork variance and 55.8% of team effectiveness variance (R² = 0.558), with an acceptable SRMR value of 0.059. The mediation test indicates partial mediation, with teamwork explaining 60.4% of the total effect. These findings suggest that gotong royong does not automatically generate effective teams. Its contribution becomes stronger when the value is expressed through practical teamwork behaviors, including coordination, communication, shared responsibility, and mutual assistance. The study extends Social Capital Theory by treating gotong royong as culturally embedded social capital and by identifying teamwork as the behavioral route through which this capital is converted into team effectiveness. Because the data were obtained from one key informant per team, the findings represent perceived team-level dynamics rather than aggregated member perceptions.